Chemical and biological stress factors on the activation of nucleopolyhedrovirus infections in covertly infected Spodoptera exigua. (17th October 2016) - Virto, C.; Navarro, D.; Tellez, M. M.; Murillo, R.; Williams, T.; Caballero, P.
Abstract: Following the consumption of baculovirus occlusion bodies (OBs), insects may succumb to lethal disease, but the survivors can harbour sublethal covert infections and may develop, reproduce and transmit the infection to their offspring. The use of different chemical and biological stressors was examined to determine whether they could be used to activate covert infections in populations of Spodoptera exigua larvae infected by the homologous nucleopolyhedrovirus (SeMNPV). Treatment of covertly infected S. exigua second instars with Tinopal UNPA‐GX, hydroxylamine, paraquat, Bacillus thuringiensis var. kurstaki crystals, spores or mixtures of crystals + spores, or a heterologous nucleopolyhedrovirus ( Chrysodeixis chalcites SNPV) did not result in the activation of SeMNPV covert infections. Similarly, virus treatments involving permissive NPVs did not result in greater mortality in covertly infected insects compared with the virus‐free controls. In contrast, 0.1% copper sulphate, 1% iron (II) sulphate and 1 mg/l sodium selenite treatments resulted in 12–41% lethal polyhedrosis disease in covertly infected larvae. A greenhouse trial using copper sulphate and sodium selenite as activation factors applied to covertly infected S. exigua larvae on sweet pepper plants resulted in very low levels of SeMNPV activation (<3%). These results highlight the important roles of copper, iron and selenium in insect immunity and baculovirus‐induced disease. However, these substances seem unlikely to prove useful for the activation of covert SeMNPV infections in S. exigua larvae under greenhouse conditions.